12-17 years old soccer players' experiences in their motivational climate and its association with their achievement goal orientation, motivation and perceived competence - Kyllönen, Anna-Pauliina (Haaga-Helia ammattikorkeakoulu, 2017)
Motivational climate plays a big role in young athlete’s sporting career and the coach has an important role in creating it. The aim of this research was to study how 12-17 years old, female and male soccer players experience their motivational climate and is it associated with their goal orientation, motivation and perceived competence. A total of 964 participants took part in this research, 286 female players and 678 male players. All participants were from some of the highest ranking soccer clubs in Finland. The data was collected in Sami Hyypiä Academy’s player development camps in 2015, where the participating players attended twice a year, once in autumn and once in spring. The participants filled out questionnaires regarding their perceived motivational climate, achievement goal orientation, motivation and perceived competence. The data from these questionnaires was then analysed using the SPSS bivariant correlation coefficient analysis, independent sample t-test and one way ANOVA t-test. The study showed that 12-17 years old, female and male soccer players experience their motivational climate more often as task involving than ego involving. Female players experience less ego involvement than male players. The study indicated that task involving motivational climate had a positive association with enjoying the practice, social relatedness, autonomy, mastery approach goal orientation, intrinisc motivation, defence skills offence skills, 1vs1 skills and identified regulation and negative association with amotivation and external regulation. Ego involving motivational climate had a positive association with performance approach goal orientation, performance avoidance goal orientation and introjected regulation. According to the results, players who operate in task involving motivational climate enjoy the practice more and feel more socially related. Task involving climate also supports intrinsic motivation and mastery goal orientation more than ego involving climate. Players who operate in ego involving ...